2018
DOI: 10.1128/mbio.02188-17
|View full text |Cite
|
Sign up to set email alerts
|

Novel (p)ppGpp Binding and Metabolizing Proteins of Escherichia coli

Abstract: The alarmone (p)ppGpp plays pivotal roles in basic bacterial stress responses by increasing tolerance of various nutritional limitations and chemical insults, including antibiotics. Despite intensive studies since (p)ppGpp was discovered over 4 decades ago, (p)ppGpp binding proteins have not been systematically identified in Escherichia coli. We applied DRaCALA (differential radial capillary action of ligand assay) to identify (p)ppGpp-protein interactions. We discovered 12 new (p)ppGpp targets in E. coli that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
172
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(178 citation statements)
references
References 72 publications
(113 reference statements)
5
172
0
1
Order By: Relevance
“…Given these observations, we wished to identify the component(s) of the translation machinery that is (are) targeted by ppGpp. The translational GTPases EF-Tu, EF-G and IF2 as well as the ribosome associated GTPases including Obg (Buglino et al, 2002; Feng et al, 2014), RsgA (Corrigan et al, 2016; Zhang et al, 2018), RbgA (Corrigan et al, 2016; Pausch et al, 2018), Era (Corrigan et al, 2016), and HflX (Corrigan et al, 2016; Zhang et al, 2018) have all been reported to bind (p)ppGpp. However, (p)ppGpp inhibits protein synthesis by the PURExpress system (Figure 4), which contains only IF2, EF-Tu, and EF-G, so inhibition of one or more of these proteins is likely sufficient to account for the in vivo inhibitory effect of (p)ppGpp on translation.…”
Section: Resultsmentioning
confidence: 99%
“…Given these observations, we wished to identify the component(s) of the translation machinery that is (are) targeted by ppGpp. The translational GTPases EF-Tu, EF-G and IF2 as well as the ribosome associated GTPases including Obg (Buglino et al, 2002; Feng et al, 2014), RsgA (Corrigan et al, 2016; Zhang et al, 2018), RbgA (Corrigan et al, 2016; Pausch et al, 2018), Era (Corrigan et al, 2016), and HflX (Corrigan et al, 2016; Zhang et al, 2018) have all been reported to bind (p)ppGpp. However, (p)ppGpp inhibits protein synthesis by the PURExpress system (Figure 4), which contains only IF2, EF-Tu, and EF-G, so inhibition of one or more of these proteins is likely sufficient to account for the in vivo inhibitory effect of (p)ppGpp on translation.…”
Section: Resultsmentioning
confidence: 99%
“…There are several other recently identified (p)ppGpp targets that contain the PRPP binding motif, including the phosphoribosyltransferases XGPRT, UPRT, and PurF from E. coli 6,19,20 . All these enzymes bind PRPP as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Mutant strains lacking both relP and relQ have reduced survival activities in response to antibiotic agents that induce cell-envelope 'stresses', such as ampicillin and vancomycin [37]. In other Firmicutes taxa that contain SAS homologues whose alarmonesynthesizing activities have been determined, such as E. faecalis, S. mutans and B. subtilis; the rsh gene is non-essential for viability [34,63,64], suggesting that there may be alternative pathways for (pp)pGpp hydrolysis, such as small alarmone hydrolases (SAHs) [14,65], NUDIX hydrolases (Ndx8, MutT, NudG) [66,67], or phosphohydrolases belonging to a variety of families (e.g. Mesh1, TrmE, NadR, PhoA, UshA) [67,68].…”
Section: Discussionmentioning
confidence: 99%